Platelet-targeted hyperfunctional FIX gene therapy for hemophilia B mice even with preexisting anti-FIX immunity - Schroeder, Jocelyn A. (Blood Adv, 2021)
Gene therapy may lead to a cure for hemophilia B (HB) if it is successful. Data from clinical trials using adeno-associated virus (AAV)–mediated liver-targeted FIX gene therapy are very encouraging. However, this protocol can be applied only to adults who do not have liver disease or anti-AAV antibodies, which occur in 30% to 50% of individuals. Thus, developing a protocol that can be applied to all HB patients is desired. Our previous studies have demonstrated that lentivirus-mediated platelet-specific FIX (2bF9) gene therapy can rescue bleeding diathesis and induce immune tolerance in FIX(null) mice, but FIX expression was only ∼2% to 3% in whole blood. To improve the efficacy, we used a codon-optimized hyperfunctional FIX-Padua (2bCoF9R338L) to replace the 2bF9 cassette, resulting in 70% to 122% (35.08-60.77 mU/10(8) platelets) activity levels in 2bCoF9R338L-transduced FIX(null) mice. Importantly, sustained hyperfunctional platelet-FIX expression was achieved in all 2bCoF9R338L-transduced highly immunized recipients with activity levels of 18.00 ± 9.11 and 9.36 ± 12.23 mU/10(8) platelets in the groups treated with 11 Gy and 6.6 Gy, respectively. The anti-FIX antibody titers declined with time, and immune tolerance was established after 2bCoF9R338L gene therapy. We found that incorporating the proteasome inhibitor bortezomib into preconditioning can help eliminate anti-FIX antibodies. The bleeding phenotype in 2bCoF9R338L-transduced recipients was completely rescued in a tail bleeding test and a needle-induced knee joint injury model once inhibitors dropped to undetectable. The hemostatic efficacy in 2bCoF9R338L-transduced recipients was further confirmed by ROTEM and thrombin generation assay (TGA). Together, our studies suggest that 2bCoF9R338L gene therapy can be a promising protocol for all HB patients, including patients with inhibitors.